IN VITRO STUDY OF ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF OXALIC ACID-DERIVED BIOACTIVE CHELATING AGENT - SELASTEEN F, DAISY; RAJ S, ALFRED CECIL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study is to evaluate the biological potentials of sodium cadmium oxalate dihydrate complex prepared by a single diffusion method in the silica gel medium. Methods: The present complex was derived by the oxalic acid using a single diffusion method in gel medium and tested for single-crystal X-ray diffraction, ultraviolet-visible (UV) spectrum (190–500 mm), and solubility (distilled water at 20–29°C) studies. Antioxidant activity was determined by 2, 2-diphenyl-1-picrylhydrazyl assay, and antimicrobial activity was measured by agar well diffusion method. Results: The present chelating complex was successfully synthesized by gel technique. The solubility of sodium cadmium oxalate dihydrate was moderately good for deionized warm water. The UV spectral studies confirmed the chelating O-H, Na-O, and C-O bonds of the newly synthesized complex for the optical and biological properties. Conclusions: The metal-oxygen and oxygen-hydrogen bonds of the present newly synthesized sample much improved its optical, antimicrobial, and antioxidant activities and find its applications in the field of pharmaceutical and biomedical applications.